Diaporthe citri: A Fungal Pathogen Causing Melanose Disease - Chingchai Chaisiri; Xiangyu Liu; Yang Lin; Chaoxi Luo (Plants, 2022)
Citrus melanose is a fungal disease caused by Diaporthe citri F.A. Wolf. It is found in various citrus-growing locations across the world. The host range of D. citri is limited to plants of the Citrus genus. The most economically important hosts are Citrus reticulata (mandarin), C. sinensis (sweet orange), C. grandis or C. maxima (pumelo), and C. paradisi (grapefruit). In the life cycle of D. citri throughout the citrus growing season, pycnidia can be seen in abundance on dead branches, especially after rain, with conidia appearing as slimy masses discharged from the dead twigs. Raindrops can transmit conidia to leaves, twigs, and fruits, resulting in disease dispersion throughout small distances. Persistent rains and warm climatic conditions generally favor disease onset and development. The melanose disease causes a decline in fruit quality, which lowers the value of fruits during marketing and exportation. High rainfall areas should avoid planting susceptible varieties. In this article, information about the disease symptoms, history, geographic distribution, epidemiology, impact, and integrated management practices, as well as the pathogen morphology and identification, was reviewed and discussed.